Enhanced performance in capacitive force sensors using carbon nanotube/polydimethylsiloxane nanocomposites with high dielectric properties. Issue 10 (22nd February 2016) - Jang, Hyeyoung; Yoon, Hyungsuk; Ko, Youngpyo; Choi, Jaeyoo; Lee, Sang-Soo; Jeon, Insu; Kim, Jong-Ho; Kim, Heesuk
Abstract : A force sensor array composed of alkylamine-MWCNT/PDMS composites shows enhanced performance and remarkable stability at heavy input loadings. Abstract : Force sensors have attracted tremendous attention owing to their applications in various fields such as touch screens, robots, smart scales, and wearable devices. The force sensors reported so far have been mainly focused on high sensitivity based on delicate microstructured materials, resulting in low reproducibility and high fabrication cost that are limitations for wide applications. As an alternative, we demonstrate a novel capacitive-type force sensor with enhanced performance owing to the increased dielectric properties of elastomers and simple sensor structure. We rationally design dielectric elastomers based on alkylamine modified-multi-walled carbon nanotube (MWCNT)/polydimethylsiloxane (PDMS) composites, which have a higher dielectric constant than pure PDMS. The alkylamine-MWCNTs show excellent dispersion in a PDMS matrix, thus leading to enhanced and reliable dielectric properties of the composites. A force sensor array fabricated with alkylamine-MWCNT/PDMS composites presents an enhanced response due to the higher dielectric constant of the composites than that of pure PDMS. This study is the first to report enhanced performance of capacitive force sensors by modulating the dielectric properties of elastomers. We believe that the disclosed strategy to improve the sensor performance by increasing the dielectric properties of elastomers has great potential in the development of capacitive force sensor arrays that respond to various input forces.